Genetic diversity of influenza A(H3N2) viruses in Northern Cameroon during the 2014‐2016 influenza seasons. Issue 8 (25th March 2019) - Njifon, Hermann Landry Munshili; Monamele, Chavely Gwladys; Vernet, Marie‐Astrid; Njankouo, Mohamadou Ripa; Deweerdt, Louis; Nono, Raphael; Kenmoe, Sebastien; Mbacham, Wilfred; Njouom, Richard
Abstract: In Cameroon, genome characterization of influenza virus has been performed only in the Southern regions meanwhile genetic diversity of this virus varies with respect to locality. The Northern region characterized by a Sudan tropical climate might have distinct genetic characterization. This study aimed to better understand the genetic diversity of influenza A(H3N2) viruses circulating in Northern Cameroon. Sequences of three gene segments (hemagglutinin (HA), neuraminidase (NA) and matrix (M) genes) were obtained from 16 A(H3N2) virus strains collected during the 2014 to 2016 influenza seasons in Garoua. The HA gene segments were analysed with respect to reference strains while the NA and M gene was analysed for reported genetic markers of resistance to antivirals. Analysis of the HA sequences revealed that majority of the virus strains grouped together with the 2016‐2017 vaccine strain (3C.2a‐A/Hong Kong/4801/2014) while 3/5 (60%) of the 2015 viral strains grouped together with the 2015‐2016 vaccine strain 3C.3a‐A/Switzerland/9715293/2013. Within clade 3C.2a, Northern Cameroon sequences mostly grouped in sub‐clade A3 (10/16). Analysis of the coding regions of the NA and M genes showed that none had genetic markers of resistance to neuraminidase inhibitors but all strains possessed the S31N substitution of resistance to amantadine. Due to some discrepancies observed in this region with respect to the Southern regions of Cameroon, there is necessity of including all regions within a country in the sentinel surveillance of influenza. These data will enable to track changes in influenza viruses in Cameroon.